2021
DOI: 10.1182/blood.2020009779
|View full text |Cite|
|
Sign up to set email alerts
|

P-selectin deficiency promotes liver senescence in sickle cell disease mice

Abstract: Sickle cell disease (SCD) is caused by a homozygous mutation in the β-globin gene, which leads to erythrocyte sickling, vaso-occlusion, and intense hemolysis. P-selectin inhibition has been shown to prevent vaso-occlusive events in SCD patients, however, the chronic effect of P-selectin inhibition in SCD remains to be determined. Here, we used quantitative liver intravital microscopy in our recently generated P-selectin deficient SCD mice to show that chronic P-selectin deficiency attenuates liver ischemia, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“… 32 Previously we 19 and others 33 showed increased expression of leukocytes (monocytes and macrophages) in SCD mouse liver, a phenomenon significantly reduced in SCD mice following P-selectin deletion (SCD; Selp -/- mice). 34 Interestingly, we have also found that chronic P-selectin deficiency in SCD mice exacerbates overall liver senescence and injury. 34 Thus, we hypothesized that the increased liver damage seen in SCD; Selp -/- mice is most likely due to enhanced LSEC senescence.…”
Section: Resultsmentioning
confidence: 71%
“… 32 Previously we 19 and others 33 showed increased expression of leukocytes (monocytes and macrophages) in SCD mouse liver, a phenomenon significantly reduced in SCD mice following P-selectin deletion (SCD; Selp -/- mice). 34 Interestingly, we have also found that chronic P-selectin deficiency in SCD mice exacerbates overall liver senescence and injury. 34 Thus, we hypothesized that the increased liver damage seen in SCD; Selp -/- mice is most likely due to enhanced LSEC senescence.…”
Section: Resultsmentioning
confidence: 71%
“…65 However, it is important to note that long-term P-selectin deficiency was shown to reduce immune cell recruitment to the liver increasing cellular senescence and reducing epithelial cell proliferation, thereby impairing the resolution of inflammation in SCD mice. 84 Therefore, the contribution of immune cells to resolution of inflammation during hemolysis should be taken into consideration in long-term therapies in hemolytic diseases.…”
Section: Endothelial Cells As a Target Of Hemolysismentioning
confidence: 99%
“…Moreover, blocking receptor binding with antibody targeting the C5a receptor antagonizes upregulation of endothelial adhesion molecules including VCAM-1, ICAM-1, and E-selectin in liver and lungs. It is noteworthy that a P-selectin deficient SCD mouse model revealed that chronic P-selectin deficiency attenuated liver ischemia but did not resolve cellular senescence and reduced epithelial cell proliferation necessary to maintain hepatic homeostasis (74). Complement from human sera has also been shown to stimulate expression of E-selectin in porcine endothelial cells (75).…”
Section: Targeted Therapeutics Against Leukocyte and Platelet Activation In Vaso-occlusive Crisismentioning
confidence: 99%